Macrozoobenthos Community Structure at Teluk Marunggai Beach, Nagari Sungai Nyalo, Pesisir Selatan District, West Sumatera Province - Ariaz, Panji Ahmad; Zulkifli, Zulkifli; Efriyeldi, Efriyeldi (Tropical Marine Environmental Sciences, 2024)
Teluk Marunggai Beach, Nagari Sungai Nyalo, is one of the new tourist areas in Pesisir Selatan Regency which, over time, will begin to be in demand by tourists, which will have an impact on the life of the biota on the beach, one of which is macrozoobenthos. This research was conducted in March 2023 in the Intertidal Zone of Teluk Marunggai Beach, Sungai Nyalo Village, Koto Ampek Tarusan District, Pesisir Selatan Regency, West Sumatra Province. The purpose of this study was to determine the type and abundance of macrozoobenthos species in the coastal waters of Marunggai Bay and to determine the diversity, uniformity, dominance and distribution patterns of macrozoobenthos in the coastal waters of Marunggai Bay. The research method used is the survey method, where the sampling using the quadrant transect method is carried out at three stations. The research results found 40 species of macrozoobenthos. The most common species found at all stations were Turbo cinereus from the Turbinidae family and the Gastropod class. The macrozoobenthos abundance values ​​obtained ranged from 6.44–6.67 ind/m2. Species diversity index values ​​ranged from 3.06–3.52, namely high. Uniformity index values ​​ranged from 3.02 to 3.14, high uniformity, dominance index values ​​ranged from 0.10 to 0.15; no species dominated, and the value of the distribution pattern ranged from 2.959 to 2.962 with a group distribution pattern